Determinant physical factors of tennis serve velocity: a brief review - Colomar, J.; Corbi, F.; Brich, Q.; Baiget, E. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To review the main physical aspects that could positively or negatively influence serve velocity (SV).